Mechanisms of acute knee injuries in bouldering and rock climbing athletes - Lutter, C.; Tischer, T.; Cooper, C.; Frank, L.; Hotfiel, T.; Lenz, R.; Schöff, V. (The American Journal of Sports Medicine, 2020)
Background:There is limited insight into the mechanisms of knee injuries in rock climbing and bouldering in noncompetitive andcompetitive athletes.Purpose:To examine the traumatic mechanisms of injury, demographics, distribution, and severity of knee injuries in affected athletes. Study Design:Case series; ' Level of evidence, 4. Methods:During a 4-year period, we performed a retrospective multicenter analysis of acute knee injuries in competitive andnoncompetitive climbing athletes. Traumatic mechanisms were inquired and severity levels, therapies, and outcomes recordedwith visual analog scale, Tegner, Lysholm, and climbing-specific outcome scores. Results:Within the observation period, 71 patients (35% competitive athletes, 65% noncompetitive athletes) with 77 indepen-dent acute knee injuries were recorded. Four trauma mechanisms were identified: high step (20.8%), drop knee (16.9%), heelhook (40.3%), and (ground) fall (22.1%). The leading structural damage was a medial meniscal tear (28.6%), found significantlymore often in the noncompetitive group. A specific climbing injury is iliotibial band strain during the heel hook position. Most injuries resulted from indoor bouldering (46.8%). Surgical procedures were predominantly necessary in noncompetitive climbers. One year after the injury, the Tegner score was 5.960.8 (mean6SD; range, 3-7); the Lysholm score was 9764.8 (range,74-100); and the climbing-specific outcome score was 4.860.6 (range, 2-5). Conclusion:Increased attention should be placed on the climber`s knee, especially given the worldwide rise of indoor bouldering. Sport-specific awareness and training programs for noncompetitive and competitive climbing athletes to reduce knee injuries should be developed, and sports medical supervision is mandatory